Predictors of asynchronies during assisted ventilation and its impact on clinical outcomes: The EPISYNC cohort study - Sousa, Mayson Laércio de Araújo; Magrans, Rudys; Hayashi, Fátima K.; Blanch, Lluís; Kacmarek, Robert M.; Ferreira, Juliana C. (Journal of critical care, 2020)
To investigate if respiratory mechanics and other baseline characteristics are predictors of patient-ventilator asynchrony and to evaluate the relationship between asynchrony during assisted ventilation and clinical outcomes. We performed a prospective cohort study in patients under mechanical ventilation (MV). Baseline measurements included severity of illness and respiratory mechanics. The primary outcome was the Asynchrony Index (AI), defined as the number of asynchronous events divided by the number of ventilator cycles and wasted efforts. We recorded ventilator waveforms throughout the entire period of MV. We analyzed 11,881 h of MV from 103 subjects. Median AI during the entire period of MV was 5.1% (IQR:2.6–8.7). Intrinsic PEEP was associated with AI (OR:1.72, 95%CI:1.1–2.68), but static compliance and airway resistance were not. Simplified Acute Physiology Score 3 (OR:1.03, 95%CI:1–1.06) was also associated with AI. Median AI was higher during assisted (5.4%, IQR:2.9–9.1) than controlled (2%, IQR:0.6–4.9) ventilation, and 22% of subjects had high incidence of asynchrony (AI≥10%). Subjects with AI≥10% had more extubation failure (33%) than patients with AI<10% (6%), p = .01. Predictors of high incidence of asynchrony were severity of illness and intrinsic PEEP. High incidence of asynchrony was associated with extubation failure, but not mortality. Trial registration: ClinicalTrials.gov, NCT02687802 •Intrinsic PEEP at intubation was a predictor of high incidence of asynchrony (AI≥10%), but static compliance and airway resistance were not•Severity of illness was also associated with high incidence of asynchrony•Double triggering was the most frequent type of asynchrony in subjects under controlled ventilation.•During assisted ventilation, ineffective efforts were more common.•AI≥10% during assisted ventilation was associated with extubation failure, but not with mortality